Pituitary imaging using a labelled somatostatin analogue in acromegaly. - Ur, E; Mather, S; Bomanji, J; Ellison, D; Britton, K; Grossman, AB; Wass, J; Besser, G (1992)
OBJECTIVE: A number of neoplasms are known to express somatostatin receptors, and the use of somatostatin receptor imaging in their localization has recently been described. We have looked at the use of an 123I-labelled Tyr3-octreotide analogue of somatostatin in the visualization and functional characterization of growth hormone-secreting pituitary adenomas. PATIENTS: Fifteen patients with biochemically-proven acromegaly were scanned using this agent. In eight of these we also assessed acute GH responses to octreotide in order to correlate these responses with tumour uptake characteristics. MEASURES: Planar and single-photon-emission computerized tomographic (SPECT) images of the head were obtained using a gamma-camera at 10 minutes, and 4 and 24 hours, after injection of the radiopharmaceutical. Blood for serum GH was sampled for 12 hours after administration of a single dose of 100 micrograms octreotide. RESULTS: Twelve of the acromegalic subjects showed significant uptake of the radiopharmaceutical in the pituitary fossa. Of the eight patients in whom we assessed acute GH responses, five demonstrated a significant fall in GH in response to octreotide. These subjects also showed positive uptake in the pituitary on scanning. The three patients who had no fall in GH had no uptake on scanning. CONCLUSIONS: Uptake of 123I-labelled Tyr3-octreotide in the pituitary fossa appears to correlate closely with the presence of a therapeutic response to octreotide.